MODEL PEMBELAJARAN BERBASIS LEARNING MANAGEMENT SYSTEM DENGAN PENGEMBANGAN SOFTWARE MOODLE DI SMA NEGERI KOTA YOGYAKARTA - Raharja, Setya (Universitas Negeri Yogyakarta, 2011)
This study is aimed at finding out the condition, readiness, and the needs for hardware, software, and brainware in schools to support the development of e-learning systems and developing a model of Moodle software development for e-learning suitable with the needs of state senior high schools in Yogyakarta. The study uses the Research Development approach, with the research setting of high school e-learning in Yogyakarta. The respondents are school principals and staff members who deal with information technology in the school. Data are collected by interview, observation, and documentation; and are analyzed qualitatively. The results show: (1) The condition, readiness, and needs indicate that the hardware and software meet the basic criteria, while human resources have not met the number and qualifications, both for computer experts and technicians. (2) Based on the condition, readiness, and needs, a preliminary design of LMS-based learning model is developed the with the development of Moodle software for the e-learning system of state high schools in Yogyakarta. The development involves modifying the Moodle software that emphasizes the facility of plug-ins (dragMath), hosting, and maintenance. The designed model is validated by experts and socialized and trained to the IT administrative members of the state high schools. The model developed receives positive responses from schools and is to be followed up with the development of content subjects included in the e-learning